Manajemen Pengolahan Air Limbah Industri di Kawasan Industri Medan - Muhammad Amirul Arif; Ilmi Abdullah; Erinsyah Maulia Rangkuti; Zainal Zainal (Politeknik Ganesha Medan, 2021)
The Medan Industrial Estate which is close to residential areas will certainly cause many problems that must be addressed including air, water, soil and noise pollution. The pollution has a direct impact on residential areas near the Industrial Estate, especially the residents of Deli Serdang Regency, Percut Sei Tuan District, North Sumatra Province. PT Kawasan Industri Medan is trying to overcome this problem by making management changes including changes in the organizational structure and changes in the waste management system where it is expected that the management changes made can meet the quality standards set by the government. This study aims to determine and analyze how the management of PT KIM manages liquid waste so that it can meet the Waste Water Quality Standards implemented by the Government through the Minister of Environment Regulation No. 3 of 2010. The research method is carried out through exploration of the interests of handling and managing industrial waste. in the industrial area. Exploration of this goal uses FGD design and in-depth interviews to formulate the identification of important factors related to the handling and management of industrial waste in the Medan industrial area. The results of the wastewater managed by PT. KIM has met the quality standards set by the Government. There was an increase in wastewater capacity from 5000 m3/month to 8000 m3/month. There has been a small percentage of complaints from the surrounding community as well as from environmentalists and environmental service supervisors